PERAN PEMERINTAH DALAM PENANGGULANGAN SAMPAH DOMESTIK DI KABUPATEN KEPULAUAN SELAYAR - Aspirani, Tri Lara; Fatmawati, Fatmawati; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this study was to determine the role of the village government in dealing with domestic waste in Kembang Ragi Village, Selayar Islands Regency. This type of research is qualitative research, data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction and conclusion. The results of the study show that the government's role as a regulator does not yet have village regulations made by the village government, so it still needs to be socialized with the community regarding waste management. The government's role as a dynamicator is that the government always provides appeals, invitations and directions. The government's role as a facilitator is the first, the government always socializes the problem of waste management. The government's role as an innovator is to provide ideas to the community by recycling waste into something that can be reused. The government's role as a catalyst is that in government socialization it is always emphasized to the community